Pemerolehan Bahasa Anak Usia 5 Tahun (Studi Kasus :Tinjauan Psikolinguistik) - Tara, Firman; Wahyuni, Uli (Jurnal Ilmiah Dikdaya, 2022)
The purpose of this study was to describe the acquisition of phonology, syntax, and semantics of children aged 5 years. This type of research is a qualitative research using descriptive method. The subject of this research is a child named Fiorenza Gizkatara, who is five years old (5 years old). The main instrument in this research is the researcher himself. To facilitate researchers in collecting data, the researchers used auxiliary instruments in the form of interview guidelines, recordings, and reports. The results showed, (1) Eza's semantic acquisition with the hypothesis theory of semantic features can be stated to be in the generalization stage. Children of this age are able to express words from the point of view of their perception that objects have the same semantic features. (2) Eza's phonological acquisition is stated to be good, although there are some letters that are not correct in the pronunciation of sounds in the pronunciation of certain words. (3) Eza's syntactic acquisition is stated to be good, because it can be identified the types of sentences that he often used